Does Arthroscopic Rotator Cuff Repair Improve Kinesiophobia, Depression, and Spatiotemporal Parameters in the Long Term? - Deniz, Gulnihal; Bilek, Furkan; Esmez, Omer; Gulkesen, Arif; Gurger, Murat (Erciyes Univ Sch Medicine, 2023)
Objective: This study aimed to investigate the long-term effects on pain, kinesiophobia, depression, functional capacity, balance, mobility, and spatiotemporal parameters in individuals who underwent rotator cuff (RC) surgery.Materials and Methods: Measurements were conducted on 45 individuals recommended for RC arthroscopy. These included bilateral upper extremity range of motion (ROM), muscle strength, bilateral hand grip strength, spatiotemporal parameters, 9-hole peg test (9-HPT), Beck Depression Inventory (BDI), Tampa Scale of Kinesiophobia (Tampa), Shoulder Pain and Disability Index (SPADI), and Constant-Murley Score. All measurements were taken one week before and six months after the arthroscopic intervention.Results: Post-RC arthroscopy results showed significant improvements in upper extremity ROM, muscle strength, hand grip strength, 9-HPT, Tampa, BDI, SPADI, and Constant-Mur-ley Score compared to pre-arthroscopy measurements. Spatiotemporal parameters such as total weight transfer, step cycle duration, double stance duration, step length, gait cycle length, foot angle, and cadence values were highly significant in both operated and non-operated extremities after arthroscopic surgery (p<0.01). However, hindfoot pressure analysis and swing phase values were significant only on the operated side after arthroscopic surgery (p<0.05).Conclusion: Prior to RC arthroscopy, individuals exhibited kinesiophobia, depression, reduced functional capacity, balance asymmetry, decreased mobility, and, consequently, spatiotemporal parameter asymmetry between the extremities. Gait disturbances (lengthened swing phase, decreased step length, increased foot angle), balance loss, and arm sway asymmetry were also evident before RC arthroscopy. Based on these findings, we suggest incorporating balance and gait training into the early rehabilitation program after RC arthroscopy.
Keywords: Rotator cuff; kinesiophobia; gait analysis; arthroscopy; balance